Klippel–Trénaunay syndrome with profound abdominal lymphatic-venous malformation in a three-day-old newborn: a case report and literature review - Wei, Shih Yang; Liu, Yu Peng; Lin, Dao Chen; Tsai, Pei Shan (Frontiers in Pediatrics, 2024)
Background: Klippel-Trénaunay syndrome, a kind of congenital limb-length-discrepancy disorder, is commonly associated with a variety of vascular anomalies.We present the case of a three-day-old newborn with a profound abdominal mass lesion during prenatal magnetic resonance imaging (MRI) examination. After delivery, physical examination revealed mild hemihypertrophy of the left lower extremity and red lesions on the left thigh. MRI of the abdomen showed a cyst-like lesion measuring 6.3 × 2.7 × 5.5 cm in the upper abdomen. Within the mass, there were also some possible calcified spots exhibiting high T1WI signals and low T2WI signals. A computed tomography (CT) scan of the abdomen was consistent with an ill-defined cystic tumor with small calcifications and encasement of mesenteric vessels. A MRI of the left lower extremity showed a tubular structure with a signal void and homogeneous strong enhancement located in the anterior subcutis of the left lower limb. The CT scan confirmed that the tubular structure was consistent with a venous malformation. This patient had features of Klippel-Trénaunay syndrome, including port-wine stains, a profound abdominal mass, and vascular malformations of the left lower extremity.In this article, we presented a case of Klippel-Trénaunay syndrome, emphasizing both prenatal and confirmatory postnatal cross-sectional imaging findings. The rare presentation of an abdominal lymphatic-venous formation played a pivotal role as a crucial indicator for an early diagnosis of Klippel-Trénaunay syndrome.